Nutritional Value and Physical Quality of Oral Nutritional Supplements Made from Purple Sweet Potatoes to Treat Malnutrition in Patients with Cancer - Kurniasari, Fuadiyah N.; Susetyowati, Susetyowati; Hardianti, Mardiah Suci; Cempaka, Anggun Rindang (Current Nutrition & Food Science, 2024)
Background: Malnutrition often occurs in patients with cancer, which eventually leads to decreasing response to therapy and increased morbidity and mortality rate. Oral Nutrition Supplements (ONS) are necessary to provide additional nutritional intervention to prevent and treat malnutrition in cancer patients. Purple sweet potato is a local food that is abundantly available in Indonesia and can be utilized as a basic ingredient for producing a modified ONS formula that is not only high in nutritional value but also has good physical quality.Objective: This study aimed to evaluate the nutritional value and physical quality of purple sweet potato-based ONS.Methods: A new local food-based formula was formulated by using purple sweet potato as the main ingredient. This new formula, which was then mentioned as the treatment formula, was subsequently compared with the control formula. The control formula was made from ingredients commonly used for producing ONS in hospitals in Indonesia, such as milk powder, sugar, oil, and other additives such as maltodextrin and creamer. Meanwhile, the treatment formula was labelled into three treatment formulas based on the differences in the proportions of white egg flour and whey protein as a protein source in each treatment formula. The treatment formula was formulated by using local ingredients of purple sweet potato flour and egg white flour by adding whey protein, extra virgin olive oil, omega-3 powder, sugar, and creamer. A proximate analysis was conducted to analyze the nutrient content of the formula and the viscosity and osmolarity tests were conducted to evaluate the physical qualities of the formula. The laboratory analysis results were described as descriptive data, then analyzed by using One-Way ANOVA. The determination of the best treatment formula in the form of effectiveness (Nh).Results: The results of the proximate test and physical quality showed that the best formula based on the highest Nh value of 0.75 was P3 with 245 kcal energy, 8.8 g (14%) protein, 6.5 g (24%) fat, and 37.8 g (62%) carbohydrate, viscosity 28.1 cP, and osmolarity 492.3 mOsm (iso-osmolar) per serving size (200 ml).Conclusion: Formula P3 which contains more egg white flour than whey protein is the best formula that has the best nutritional value and good physical quality.
Keywords: malnutrition